ANALISIS STABILITAS TIMBUNAN DI ATAS KONSTRUKSI TIANG DAN GEOSINTETIK MENGGUNAKAN PROGRAM ELEMEN HINGGA - Yosia Firmansyah; Andryan Suhendra (Prodi Sarjana Teknik Sipil, FT, Universitas Tarumanagara, 2020)
soft soil is a challenge for geotechnical engineer due to the characteristics of the soil that cause over settlement. Geosynthetic reinforcement is used on piles to correct undesirable soft soil characteristics. This thesis will use the BS 8006 methods and 3D software that use the finite element method to compare the geosynthetic tensile strength and how geosynthetic influences the embankment. The author will use the 3D software in the hope that it will produce a more accurate analysis compared to the 2D software. This thesis will compare the calculation of the geosynthetic tensile strength with the finite element method and the BS 8006 method. This is done because the calculation method BS 8006 does not take into account the subgrade in analyzing the geosynthetic tensile strength. This geosynthetic material has been proven to reduce slippage and channel load to the pile. This reinforcement of poles and geocyntetics can increase embankment safety factor by at least 0.35.